Innovation, Market Orientation, and Organizational Learning: An Integration and Empirical Examination - Hurley, Robert F.; Hult, G. Tomas M. (Journal of Marketing, 1998)
Research on market orientation and organizational learning addresses how organizations adapt to their environments and develop competitive advantage. A significant void exists in current models of market orientation because none of the frameworks incorporates constructs related to innovation. The authors present a conceptual framework for incorporating constructs that pertain to innovation in market orientation research. Some of the critical relationships in this conceptual framework are tested among a sample of 9648 employees from 56 organizations in a large agency of the U.S. federal government. The results indicate that higher levels of innovativeness in the firms’ culture are associated with a greater capacity for adaptation and innovation (number of innovations successfully implemented). In addition, higher levels of innovativeness are associated with cultures that emphasize learning, development, and participative decision making. The authors make recommendations for incorporating constructs related to innovation into research on market orientation and organizational learning.